SKIN HEALTH SCREENING FOR FEMALE STUDENTS AT DAARUL RAHMAN ISLAMIC BOARDING SCHOOL: SKRINING KESEHATAN KULIT UNTUK REMAJA SANTRIWATI DI PESANTREN DAARUL RAHMAN - Putu Erma Pradnyani; Ima Maria; Syarif Rahman Hasibuan; Dela Riadi; Yanti Harjono; Sri Wahyuningsih (Darmabakti Cendekia: Journal of Community Service and Engagements, 2026)
Background: Skin health is an important aspect of overall health because the skin is an organ that protects against the external environment. Skin diseases can spread through the living environment, especially in crowded living spaces. Screening can help identify skin problems before they become more serious conditions. Objective: The purpose of community service at Pesantren Daarul Rahman is to conduct skin health screenings for female high school students to improve their health. Method: This implementation involves health screening, specifically for skin problems, by directly observing the skin conditions of female students who reported itching, skin spots, and skin discomfort. Methods screening is a two-stage method using (1) a self-administered questionnaire on skin conditions, and (2) physical examination. Results: Of 180 female high school students, 12.2% had skin problems. They revealed several skin problems: 15 female students had scabies, 5 had a fungal infection, 1 had chicken skin, and 1 had irritant contact dermatitis. The average level of knowledge regarding the symptoms, prevention, and transmission of skin diseases was 9.05 before the educational session and increased to 9.84 after the session. Conclusion: It is hoped that the screening conditions from this community service will serve as initial data for the health of female students in the pesantren. Early screening for skin health issues will help Islamic boarding schools prevent the spread of skin diseases, such as scabies.